1987
DOI: 10.1037/0882-7974.2.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Adult age differences in the speed and capacity of information processing: II. An electrophysiological approach.

Abstract: A total of 60 subjects performed different variants of the Sternberg memory search task in an experiment designed to evaluate aging differences in the speed of the human information-processing system. The present study examined the nature of the age-related slowing using convergent methodologies of Sternberg's additive factors logic, the speed-accuracy trade-off, and the P300 component of the event-related brain potential. These methodologies revealed that a substantial component of slowing was manifest in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
68
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 47 publications
16
68
3
Order By: Relevance
“…Because the emphasis of this study is on the differential effects of AD and HD on mental rotation, specific analyses comparing the two control groups to one another were not summarized. However, clear age differences did emerge in this study, consistent with the welldocumented finding in the literature that aging is associated with slower speed of processing and reaction times on many tasks (Cerella, 1985;Salthouse & Somberg, 1982;Simon & Pouraghabagher, 1978;Strayer et al, 1987), including mental rotation (Dollinger, 1995;Dror & Kosslyn, 1994;Hertzog & Rypma, 1991;Hertzog et al, 1993;Puglisi & Morrell, 1986). Although in absolute terms HD patients were not slower than AD patients, they performed mental rotation at essentially the same speed as neurologically intact individuals that, on average, were more than 30 years older, rather than at the speed expected from individuals their age.…”
Section: Discussionsupporting
confidence: 92%
“…Because the emphasis of this study is on the differential effects of AD and HD on mental rotation, specific analyses comparing the two control groups to one another were not summarized. However, clear age differences did emerge in this study, consistent with the welldocumented finding in the literature that aging is associated with slower speed of processing and reaction times on many tasks (Cerella, 1985;Salthouse & Somberg, 1982;Simon & Pouraghabagher, 1978;Strayer et al, 1987), including mental rotation (Dollinger, 1995;Dror & Kosslyn, 1994;Hertzog & Rypma, 1991;Hertzog et al, 1993;Puglisi & Morrell, 1986). Although in absolute terms HD patients were not slower than AD patients, they performed mental rotation at essentially the same speed as neurologically intact individuals that, on average, were more than 30 years older, rather than at the speed expected from individuals their age.…”
Section: Discussionsupporting
confidence: 92%
“…There was an effect of set size on naming time, and this suggests that processes other than a memory-comparison process were affected by memory set size. Strayer et al (1987) measured the P300 response' as well as overt reaction times, and found a steeper slope for overt reaction times than for P300 latencies. Since P300 reflects preresponse processing, Strayer et al argued that response processes contributed to the set-size effect observed with overt reaction times.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, one might continue to work with the Sternberg model and argue that memory set size might affect stages other than the comparison stage (see, e.g., Kirsner, 1972;Strayer, Wickens, & Braune, 1987). Kirsner (1972) used a task in which subjects named the probe after presentation of the memory set as a control for perceptual and response factors in memory search.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Answer: Much evidence shows that older adults tend to adopt conservative strategies for performing speeded tasks (e.g., Baron & Matilla, 1989;Botwinick, 1966;Okun & Di Vesta, 1976;Rabbitt, 1979;Salthouse, 1978a;Strayer, Wickens, & Braune, 1987). Three factors could underlie this tendency.…”
Section: Question 1 6 : Do Older Adults Suffer From Goal Neglect?mentioning
confidence: 99%